Left atrial thickness and acute thermal injury in patients undergoing ablation for atrial fibrillation: Laser versus radiofrequency energies. (6th April 2021) - Gao, Xu; Chang, Dong; Bilchick, Kenneth C.; Hussain, Sarah K.; Petru, Jan; Skoda, Jan; Sediva, Luci; Neuzil, Petr; Mangrum, J. Michael
Abstract: Introduction: Thermally induced cardiac lesions result in necrosis, edema, and inflammation. This tissue change may be seen with ultrasound. In this study, we sought to use intracardiac echocardiography (ICE) to evaluate pulmonary vein tissue morphology and assess the acute tissue changes that occur following radiofrequency (RF) or laser ablation for atrial fibrillation (AF). Methods and Results: Patients with AF underwent pulmonary vein isolation (PVI) using irrigated RF or laser balloon. Pre‐ and post‐ablation ICE imaging was performed from within each pulmonary vein (PV). At least 10 transverse imaging planes per PV were evaluated and each plane was divided into eight segments. The PV/atrial wall thickness and the luminal area were measured at each segment. Twenty‐seven patients underwent PVI (15 with laser, 12 with RF). Ninety‐eight pulmonary veins were analyzed (58 PVs laser; 40 PVs RF). At baseline, there were no regional differences in PV wall thickness in the right‐sided veins. The anterior regions of left superior pulmonary vein (LSPV) and left inferior pulmonary vein (LIPV) were significantly thicker compared with the posterior and inferior regions ( p  < .01). Post‐ablation, PV wall thickness in RF group increased 24.1% interquartile range (IQR) (17.2%–36.7%) compared with 1.2% IQR (0.4%–8.9%) in laser group, p  = .004. In all PVs, RF ablation resulted in significantly greater percent increase in wall thickness compared with laser. Additionally, RF resulted in more variable changes in regional PV wall thickness; with more increases in wall thickness in anterior versus posterior LSPV (75.4 ± 58.5% vs. 46.8 ± 55.6%, p  < .01), anterior versus posterior right superior pulmonary vein (RSPV) (62.9 ± 63.9% vs. 44.6 ± 51.7%, p  < .05), and superior versus inferior RSPV (69.1 ± 45.4% vs. 35.9 ± 45%, p  < .05). There were no significant regional differences in PV wall thickness changes for the laser group. Conclusions: Rotational ICE can be used to measure acute tissue changes with ablation. Regional variability in baseline wall thickness was nonuniformly present in PVs. Acute tissue changes occurred immediately post‐ablation. Compared with laser balloon, RF shows markedly more thickening post‐ablation with significant regional variations.